Strengthening digital literacy in helping to learn during a pandemic - Hakim, Luthfi Nur; Nusantara, Henri (Universitas Pendidikan Indonesia, 2023)
The implementation of distance learning has increased the frequency of using digital technology by students and teachers. Expanding the use of digital technology needs to be balanced with efforts to increase students' and teachers' understanding of digital literacy. This article attempts to discuss how the results of strengthening digital literacy are carried out in community service programs. Socialization of the importance of digital literacy was also carried out to the school community as part of the Real Work Lecture activities conducted at SDN 158 Babakan Sari Babakan Surabaya. The method used in this research is strengthening digital literacy for students, teachers, and parents. Service activities include the socialization of digital literacy by teaching in class; outreach to students, teachers, and parents through digital media such as infographics, YouTube videos, and news articles. Spontaneous discussions with teachers regarding digital literacy. Introduction to several applications and digital media that can be used in distance learning.